The origins and determinants of the Milan Panić government in the Federal Republic of Yugoslavia in 1992 - Szczesio, Sławomir Lucjan (Balcanica Posnaniensia. Acta et studia, 2025)
The article presents the political dynamics behind the appointment of Milan Panić as prime minister of the Federal Republic of Yugoslavia (FRY) in 1992. The study emphasizes the pivotal role of Slobodan Milošević and the pressure from Western governments in this decision. Following the violent dissolution of the Socialist Federal Republic of Yugoslavia and the conflicts in Croatia and Bosnia and Herzegovina, the newly proclaimed FRY faced severe UN sanctions and international isolation. In response to mounting domestic unrest and the need to improve relations with the West, Milošević first supported Dobrica Ćosić, a respected dissident writer, for the federal presidency. He then unexpectedly nominated Panić, a Serbo-American businessman, as prime minister of the FRY. Panić’s selection was a calculated political maneuver by Milošević, aimed at navigating the deepening crises and breaking the country’s international isolation while simultaneously maintaining his own dominant position.